2020
DOI: 10.1186/s13012-020-0971-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of guideline dissemination and implementation strategies on health care professionals’ behaviour and patient outcomes in the cancer care context: a systematic review

Abstract: Background: Health care professionals (HCPs) use clinical practice guidelines (CPGs) to make evidence-informed decisions regarding patient care. Although a large number of cancer-related CPGs exist, it is unknown which CPG dissemination and implementation strategies are effective for improving HCP behaviour and patient outcomes in a cancer care context. This review aimed to determine the effectiveness of CPG dissemination and/or implementation strategies among HCPs in a cancer care context. Methods: A comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 65 publications
4
38
0
Order By: Relevance
“…Few studies used financial or organizational approaches, whereas no study used regulatory approaches. This finding was also observed in other reviews [ 29 ]. Thus, future studies should investigate the unused approaches, which may be effective for improving CPG dissemination and implementation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Few studies used financial or organizational approaches, whereas no study used regulatory approaches. This finding was also observed in other reviews [ 29 ]. Thus, future studies should investigate the unused approaches, which may be effective for improving CPG dissemination and implementation.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, the perspectives of other healthcare practitioners on barriers to the utilization of CPGs are less understood. This point was observed in similar reviews [ 29 ]. Patient-centered care requires multidisciplinary expertise.…”
Section: Discussionsupporting
confidence: 81%
“…The implementation strategies most frequently found among the high-quality CPGs were at the professional level, consisting mainly of the distribution of reference material, individual and group education of healthcare professionals, and presentation of CPG material at meetings. This is consistent with reports in previous studies ( Pantoja et al, 2017 ; Tomasone et al, 2020 ). Clinical algorithms, CPG versions directed at physicians, and material for classes, and presentations on CPGs were commonly found at the professional level.…”
Section: Discussionsupporting
confidence: 94%
“…The training of healthcare professionals, a strategy that is commonly utilized in the implementation of a CPG (Gagliardi & Alhabib, 2015), was repeated throughout the present implementation process, resulting in high percentages of healthcare professionals who became adequately trained, a factor that is positively associated with the increase in BF rates at hospitals (Tomasone et al, 2020). On the other hand, the indicators related to the users showed important changes directed at supporting and empowering the mothers who breastfed their children after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the implementation of clinical practice guidelines (CPGs) has increased in the health services as a systematic strategy that improves healthcare and patient outcomes (Hulscher & Wensing, 2020; Shekelle, Woolf, Grimshaw, Schünemann, & Eccles, 2012). A review of the literature on the implementation of CPGs showed that in the past decade, the studies have preferentially examined the implementation of CPGs dealing with chronic processes (high blood pressure, diabetes, pain, stroke, chronic obstructive pulmonary disease, cancer; Etxeberria et al, 2018; Friesen‐Storms et al, 2018; McCarter et al, 2018; Pons, Foks, Dippel, & Hunink, 2019; Shores et al, 2018; Tomasone, Kauffeldt, Chaudhary, & Brouwers, 2020). The strategies utilized were many, but the results were inconsistent, partly because the studies used strategies with very few components, the implementation of theoretical frameworks were not utilized, or an adequate evaluation of barriers was not performed (Gagliardi & Alhabib, 2015).…”
mentioning
confidence: 99%